Gestion de l’eau et projet de territoire : vers une gestion intégrée du delta du Rhône - Alain Dervieux; Geneviève Jolly; Aurélien Allouche (VertigO)
The executive water commission (CEDE) a non formal association of local water actors is commissioned to manage the water gates of the sea dike. These gates order the inflow and outflow of water between the sea and the Camargue to steady the hydrosalin amount in the large lagoons.  Owing to the layout of hydraulic works and to the risks due to the rise of sea level, CEDE is brought to manage the dynamics between the flow coming from the catchment area, both drainage of ground and rain and that which runs through this sluice.  This task requires to keep out of the conflicts that divide the territory, above all of political origin today, in order to decide, freely, on the direction of the exchanges with the sea. Decisions are always taken unanimously. CEDE is then able to fix the conditions of the global management of water, a major step towards management integrated in the territory.Two articles have been written about the global management of water in the Rhone delta. They are centred on 1/ the Contract of the Camargue delta, 2/ the Executive water commission. They show that one faces this reality not so well integrated in the end : together with the development or rice growing starting fifty years ago and the rise of sea level, water is everywhere in the Camargue all throughout the year and in all places. Of the solutions to manage this littoral hydrosystem for good mean, the establishment of adapted public polities, the taking part of all the actors in Camargue is a must.